Self Reported Sexual Abuse among a Group of Adolescents Attending Life Skills Education Workshops in Kerala - Arun B Nair and Devika J (Academic Medical Journal of India, 2014)
Child Sexual Abuse (CSA), once regarded as isolated incidences of offence, has evolved into a public health issue of epidemic propor- tions in recent times. The health impact of experiencing sexual abuse in childhood is both far-reaching and long-standing. Studies have established that experiencing sexual abuse during childhood and adolescence can adversely affect the physical health as well as mental and social wellbeing of the individual. Reports from various parts of the world have shown a dramatic increase in the prevalence of CSA. This study estimated the prevalence of CSA among 1000 children - 512 boys and 488 girls - who attended life skills education workshops in Kerala. The prevalence of CSA was found to be 38.67% among boys and 37.7% among girls.